2011
DOI: 10.1093/toxsci/kfr310
|View full text |Cite
|
Sign up to set email alerts
|

An NF-κB–Independent and Erk1/2-Dependent Mechanism Controls CXCL8/IL-8 Responses of Airway Epithelial Cells to Cadmium

Abstract: Airway epithelial cells in the lung are the first line of defense against pathogens and environmental pollutants. Inhalation of the environmental pollutant cadmium has been linked to the development of lung cancer and chronic obstructive pulmonary disease, which are diseases characterized by chronic inflammation. To address the role of airway epithelial cells in cadmium-induced lung inflammation, we investigated how cadmium regulates secretion of interleukin 8 (IL-8) by airway epithelial cells. We show that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 56 publications
5
27
0
Order By: Relevance
“…It is thought that NF-κB is generally involved in IL-8 gene expression [37], but in our study the addition of an NF-κB inhibitor did not reduce IL-17F-induced IL-8 expression. Consistent with this, previous reports have demonstrated that cadmium or rhinovirus induced IL-8 expression through an NF-κB-independent pathway in airway epithelial cells [38, 39]. Thus, the exact role of NF-κB signaling may vary depending on the cell types and stimulus used.…”
Section: Discussionsupporting
confidence: 74%
“…It is thought that NF-κB is generally involved in IL-8 gene expression [37], but in our study the addition of an NF-κB inhibitor did not reduce IL-17F-induced IL-8 expression. Consistent with this, previous reports have demonstrated that cadmium or rhinovirus induced IL-8 expression through an NF-κB-independent pathway in airway epithelial cells [38, 39]. Thus, the exact role of NF-κB signaling may vary depending on the cell types and stimulus used.…”
Section: Discussionsupporting
confidence: 74%
“…This regulation argues for CXCL8 as potential candidate for a functional, though indirect, readout of ERK phosphorylation in hepatoma cells that may be even further developed as noninvasive biomarker for response to multikinase inhibitors in the blood of patients with hepatocellular carcinoma. This hypothesis is supported by the identification of an ERK1/2-dependent mechanism of CXCL8 expression in airway epithelial cells (50). Inhibition of the p38 and ERK pathways downregulated CXCL10 and CXCL8 expression in epithelial cells (51,52).…”
Section: Discussionmentioning
confidence: 85%
“…MAPKs differentially regulate IL-8 expression depending on the cell type and the stimulus. In human airway epithelial cells, although cadmium activated ERK, p38, and JNK MAPKs, only inhibition of ERK MAPK suppressed IL-8 secretion (12). In U937 cells, Helicobacter pylori VacA protein induces IL-8 expression primarily via activation of p38 MAPK even though ERK MAPK is also activated (20).…”
Section: Discussionmentioning
confidence: 95%